Molecular characterization of an aster yellows phytoplasma associated with proliferation of periwinkle in Malaysia - Nejat, Naghmeh; Sijam, Kamaruzaman; Abdullah, Siti Nor Akmar; Vadamalai, Ganesan; Dickinson, Matthew (Academic Journals, 2010)
Madagascar periwinkle is a common decorative, easy growing and spreading perennial herb. Phyllody, virescence, proliferation, little leaf and yellowing symptoms were observed on periwinkle in Serdang and Banting, Selangor, Malaysia. Polymerase chain reaction (PCR) assays using P1/P7 universal phytoplasma primers and secA primers designed for identification and classification of phytoplasma, amplified 1.8 kb fragment that encompasses the entire 16S rRNA gene, the 16S - 23S intergenic spacer region and the beginning of the 23S rRNA gene as well as the 840 bp from part of secA gene, respectively. Sequence analysis of the 16S rDNA, 16S - 23S intergenic region and the beginning of the 23S rRNA and secA gene PCR products determined that the phytoplasma strain associated with periwinkle proliferation in Malaysia belongs to the ‘CandidatusPhytoplasma asteries’ (16Sr I-B) group of phytoplasmas. The virtual restriction fragment length polymorphism (RFLP) analysis with 10 restriction endonulease enzymes revealed identical patterns to phytoplasmas members of Aster yellows phytoplasma subgroup B. A phylogenetic tree based on 16S rDNA sequences,secA gene sequences and virtual RFLP revealed that the periwinkle proliferation phytoplasma is closely related to the subgroup 16SrI-B. Periwinkle proliferation also confirmed which 16SrI-B has wide geographical distribution and host range.